ECONOMICAL EFFECIENCY OF SUSTAINABLE LAND RESOURSE ALLOCATION (Scientific journal of the Fergana State University, 2023)
The proposals on the organization of workplaces and the increase of economic efficiency are justified; the cultivation of raw materials for industry on non-cultivated lands.